Supramolecular halogen bonding and photo-responsive transmembrane anion transporters - Bickerton, LE (2022)
This thesis describes the design, synthesis and testing of novel anion host architectures which exploit hydrogen, halogen, and chalcogen bonding for the purpose of selective and stimuli-responsive anion transport across lipid bilayer membranes.